Pengaruh Prenatal Care Yoga Terhadap Kesiapan Fisik Dan Psikologis Ibu Menghadapi Persalinan di Puskesmas Putri Ayu Kota Jambi - Gustina Gustina (Jurnal Akademika Baiturrahim Jambi, 2020)
Abstract During pregnancy there will be changes in the entire body system of the mother both physically and psychologically, it can make discomfort very disturbing during the process of pregnancy, childbirth and the puerperium. A comfortable pregnancy process without physical complaints and a smooth and easy delivery process can be supported by paying attention to 3 main aspects of pregnancy, namely the Balance of the Womb, muscles and pelvis. Prenatal Gentle Yoga helps mothers re-realize and recognize physical and psychological changes during pregnancy, and make communication and bonding with babies much closer. Prenatal Gentle Yoga is expected to help mothers prepare physically and psychologically for mothers in facing labor. Research to determine the effect of Prenatal Care Yoga on Physical and Psychological Preparation of Mothers  Childbirth. It is expected that all pregnant women can adapt to the Physical and Psychological Preparations of Women Childbirth. This study uses analytic design to determine the effect of Prenatal Care Yoga on Physical and Psychological Preparation of Mothers Childbirth. The study population was third trimester pregnant women who came to the Putri Ayu Health Center. The research sample was taken using a total sampling technique of 32 quota people. This research was carried out in February 2019 at the Puskesmas Putri Ayu Kota Jambi. There was a significant effect between prenatal care yoga on the physical and psychological readiness of mothers in facing labor, namely p-value <0,000 (95% CI). There is the effect of prenatal care yoga practice on physical and psychological readiness of mothers in facing labor.